The Application of Tableau in Teaching Narrative Reading to the 10th Grade Students of SMA Srijaya Negara Palembang - Aghni, Luluk Aulia (Global Expert: Jurnal Bahasa dan Sastra, 2024)
The objectives of this study were to find out (1) wether or not there was any difference in 10th grade students of SMA Srijaya Negara reading comprehension after they are taught by applying tableau and (2) there was any significant difference in reading comprehension achievement between the 10th grade students of SMA Srijaya Negara Palembang who are taught by using Tableau in learning narrative text and those who are not. This study used 66 students of the tenth grade students of SMA Srijaya Negara Palembang as the sample which was divided into two group, experimental and control group. Students in experimental group were given the treatment through tableau in learning narrative text. This study used one of quasi-experimental design that were pretest and posttest non equivalent control group design. The result of reading comprehension test was analyzed by using SPSS 21.0 program. The result indicated that there were any significant differences at level 0.05 found in the data which were analyzed by using paired sample t-test (t=6.670 > t-table=1.694). The result also showed that the application of tableau in teaching narrative reading could improve students’ reading comprehending of 10th grade students of SMA Srijaya Negara Palembang. Keywords: Tableau, teaching narrative text, reading comprehension